Prevalence of carbapenemase producing Enterobacterales colonization and risk factor of clinical infection - Kyoung Hwa Lee; Dokyun Kim; Jun Sung Hong; Soon Young Park; Nan Hyoung Cho; Mi Na Kim; Yun Jung Lee; Yeonji Wi; Eun Hwa Lee; Sang Hoon Han; Seok Hoon Jeong; Young Goo Song (Elsevier, 2023)
Background: Carbapenemase-producing Enterobacterales (CPE) are global concerns in infection control, and the number of CPE outbreaks in hospitals is increasing despite the strengthening of contact precautions. This study aimed to confirm the prevalence and transition rate of CPE infection from stool surveillance culture and to identify the acquisition pathway of CPE. Methods: This is a longitudinal review of patients with stool surveillance cultures at a tertiary center in Seoul, South Korea, from July 2018 to June 2020. Pulsed-field gel electrophoresis, multi-locus sequence typing, and whole genome sequencing were performed for carbapenemase-producing Klebsiella pneumoniae and Escherichia coli strains. Results: Among 1620 patients who had undergone stool CPE surveillance cultures, only 7.1% of active surveillance at the Emergency Room (ER) and 4.4% of universal surveillance in the Intensive Care Unit (ICU) were stool CPE positive. The transition rates from stool carriers to clinical CPE infections were 29.4% in the ER and 31.3% in the ICU. However, it was significantly high (55.0%) in the initial stool CPE-negative ICU patients. Among the initial stool CPE-positive patients, hypertension (61% vs. 92.3%, P = 0.004), malignancy (28.8% vs. 53.8%, P = 0.027), and mechanical ventilation (25.4% vs. 53.8%, P = 0.011) were significant risk factors for clinical CPE infection. Molecular typing revealed that sequence type (ST) 307 and ST 395 were dominant in K. pneumoniae, and ST 410 was dominant in E. coli isolates. Conclusions: Active surveillance showed a higher detection rate than universal stool CPE screening, and one-third of positive stool CPE specimens ultimately developed subsquent clinical CPE infection. According to the molecular typing of the identified CPE strains, in-hospital spread prevailed over external inflow, and the transition rate to clinical CPE was particularly high in the ICU. Therefore, in order to control CPE propagation, not only active surveillance to block inflow from outside, but also continuous ICU monitoring within the hospital is necessary.